AutoCAD cookbook for the Macintosh - DeLucchi, Christopher James (New York : Wiley, 1990)
An adaptation of the successful AutoCAD Cookbook for the IBM PC, this book will show Macintosh AutoCAD operators how to customize the software, using menus and AutoLISP, to match the designer's changing needs and work styles. The author emphasizes a 'hands-on' practical approach to problem solving, and presents over 600 examples of menu commands and AutoLISP functions.
Includes bibliographical references.
oif 19/02/15
Loan
Keywords: Computers -- Programming; AutoCAD -- (Computer program).; Macintosh (Computer) -- Programming; Engineering design -- Data processing